Linguistic stratigraphy and dialectal areas of the Basque Country on the basis of toponymic data / Estratigrafía lingüística y áreas dialectales del País Vasco con los datos de la toponimia - Abaitua, Joseba K. (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2025)
A linguistic stratigraphy is proposed for the Basque Country in which the Basque-Romance element covers the Latin and pre-Romance layer, without a break in continuity in the Romance case, but with a clear delimitation for the start of the Basque stratum. This would date, at least for the west of the territory, surely from the 8th century, given its dialectal condition, but with a very probable advance to the middle of the 6th century. Dialectal areas are visible above all in place names of Basque origin, an aspect with which the distribution of the main property suffixes (-ica, -ain, -ana, -iz) does not fully correlate. These show a much more disparate distribution, although it is also bounded on the spatial and temporal axes.